Assessment and Management of Pain and Anxiety in Pediatric Patients in Emergency - Sheikh, Zulakha Akhtar; Alam, Jehan; Shah, Ruqaya; Samreena; Ahmed, Javeria; Zain, Anosha (Indus Journal of Bioscience Research, 2024)
Objective: To assess pain level in pediatric patients presented with dental pain at the emergency department of Jinnah Postgraduate Medical Center, Karachi. Study design: A cross-sectional study. Place and Duration: The study was conducted in a Pediatric Emergency Department at the Jinnah Postgraduate Medical Center, Karachi, for 6 months from March 2024 to September 2024. Methodology: Total 230 hospitalized children over 6 months were assessed the pain levels of these children on admission and 8 hours after admission. Analgesic treatment was given to children and pain was assessed according to Wong-Baker Faces Pain Rating Scale. SPSS version 27 was used for data analysis. Descriptive statistics, such as means and standard deviations, were used to summarize the quantitative variables. Results: Paracetamol was the most given analgesic to the patients as 41.7%, whereas brufen and intravenous analgesics were given as 30.0% and 10.0%, respectively. There were 19.6% patients who had no pain at admission, 19.6% had mild pain, 37.8% had moderate pain and 23.0% had severe pain. Whereas, 110 (47.8%) patients had no pain after analgesics, 35.2% had mild pain, 13.5% and 3.5% had severe pain. The association of severity of pain at admission and after analgesics was statistically significant, (p<0.001). Conclusion: Pain scales are indeed valuable tools for assessing and managing pain in children, as they provide a standardized and systematic way to measure and communicate pain levels. Pain relief and management are important aspects of patient care, as untreated or poorly managed pain can have detrimental effects on a patient’s physical and emotional well-being.